Pengaruh Pendapatan Asli Daerah dan Pajak Daerah dan Kemiskinan pada Pertumbuhan Ekonomi di Gorontalo - Wahyuni Siregar; Fani Inka Prilia; Fatimah Fatimah; Asnidar Asnidar (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the influence of Local Own-Source Revenue (Pendapatan Asli Daerah, PAD), regional taxes, and poverty levels on economic growth in Gorontalo Province during the 2013– 2024 period. PAD and regional taxes are essential indicators of a region's fiscal independence in funding development, while poverty acts as an impediment that can reduce productivity and consumer purchasing power. The research employs quantitative analysis using secondary data obtained from the Central Bureau of Statistics (BPS) and regional financial reports. The results indicate that PAD and regional taxes have a significant positive impact on economic growth, while poverty levels have a significant negative effect. Increased PAD and regional tax revenues contribute to public investment, infrastructure development, and social services, supporting economic activities. On the other hand, high poverty levels slow down economic growth due to limited purchasing power and reduced participation in productive activities. In conclusion, optimizing PAD and regional tax management, along with effective poverty alleviation policies, is crucial to fostering inclusive and sustainable economic growth in Gorontalo. This study is expected to serve as a reference for local governments in formulating more targeted economic development strategies.